Erratum to “Inapproximability and Polynomial-Time Approximation Algorithm for UET Tasks on Structured Processor Networks” - Bouznif, M.; Giroudeau, R. (Advances in operations research, 2012)
Approximation Results If the network is a ring, there are two approximation results for Rayward-Smith's [2] algorithm as follows. (i) In the general case, the performance ratio is upper bounded by m/2+3/2-1/m , and there exists an instance for which the performance ratio is equal to m/8+1/2 [3]. (ii) If the number of processors is even, the upper-bound can be improved to 1+(3/8)m-1/2m , and there exists an instance such that the performance ratio is equal to [left ceiling]m[right ceiling] [4]. Proof. [...]nonapproximability results can be deduced.